Pengembangan Media Pembelajaran Augmented Reality Book 2 Dimensi Sub Tema Lingkungan Alam di PAUD Telkom Singaraja - Mahendra, Made Kevin Ihza; Sindu, I Gede Partha; Divayana, Dewa Gede Hendra (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2021)
The purpose ofÂ  Development The Media Learning Augmented Reality Book 2 Dimensions With The Natural Environment Theme In PAUD Telkom Singaraja is to develop 2-dimensional Augmented Reality learning media sub-theme of the natural environment on the Android platform, as a medium to facilitate the learning process and provide attractiveness in understanding the natural environment. The development of 2-dimensional Augmented Reality learning media with the sub-theme of the natural environment uses the ADDIE model which consists of stages, namely the analysis, design, development, implementation and evaluation stages. In this model, an evaluation process is carried out at each stage that is passed so as to produce learning media that suits the needs of PAUD Telkom Singaraja. The end result of this development is in the form of 2-dimensional Augmented Reality learning media with a sub-theme of the natural environment that can be used via mobile devices with the Android operating system. The black box and white box tests were carried out accordingly, the content expert test and the media test got a value of 1.00 in the very high category, the individual test got an average value of 94,22% in the very good category, the small group test got an average score of Â 94,44% with very good category student response, field test 92.89% with very good category and teacher response 90,66% with very good category.Â